Peptidomics-based identification of antihypertensive and antidiabetic peptides from sheep milk fermented using Limosilactobacillus fermentum KGL4 MTCC 25515 with anti-inflammatory activity: in silico, in vitro, and molecular docking studies - Pipaliya, Rinkal; Basaiawmoit, Bethsheba; Sakure, Amar A.; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Singh, Brij Pal; Paul, Souparno; Liu, Zhenbin; Sarkar, Preetam; Patel, Ashish; Hati, Subrota (Frontiers in Chemistry, 2024)
The present investigation focused on the synthesis of bioactive peptides from sheep milk through fermentation with Limosilactobacillus fermentum KGL4 MTCC 25515 strain and also to assess the lipase inhibition, ACE inhibition, α-glucosidase inhibition, and α-amylase inhibition activities during the fermentation process. The study observed highest activities, reaching at 74.82%, 70.02%, 72.19%, and 67.08% (lipase inhibition, ACE inhibition, αglucosidase inhibition, and α-amylase inhibition) after 48 hours at 37°C respectively. Growth optimization experiments revealed that a 2.5% inoculation rate after 48 hours of fermentation time resulted in the highest proteolytic activity at 9.88 mg/mL. Additionally, fractions with less than 3 kDa of molecular weight exhibited superior ACE-inhibition and anti-diabetic activities compared to other fractions. Fermentation of sheep milk with KGL4 led to a significant reduction in the excessive production of NO, TNF-α, IL-6, and IL-1β produced in RAW 267.4 cells upon treatment with LPS. Purification of peptides was done utilising SDS-PAGE & electrophoresis on 2D gels, identified a maximum number of bands of proteins ranging from 10 to 70 kDa. Peptide sequences were cross-referenced with AHTPDB and BIOPEP databases, confirming potential antihypertensive and antidiabetic properties. Notably, the peptide (GPFPILV) exhibited the highest HPEPDOCK score against both α-amylase and ACE.